Residual cognitive deficits 50 years after lead poisoning during childhood. Issue 7 (July 1993) - White, R F; Diamond, R; Proctor, S; Morey, C; Hu, H
Abstract : The long term neurobehavioural consequences of childhood lead poisoning are not known. In this study adult subjects with a documented history of lead poisoning before age 4 and matched controls were examined with an abbreviated battery of neuropsychological tests including measures of attention, reasoning, memory, motor speed, and current mood. The subjects exposed to lead were inferior to controls on almost all of the cognitive tasks. This pattern of widespread deficits resembles that found in children evaluated at the time of acute exposure to lead rather than the more circumscribed pattern typically seen in adults exposed to lead. Despite having completed as many years of schooling as controls, the subjects exposed to lead were lower in lifetime occupational status. Within the exposed group, performance on the neuropsychological battery and occupational status were related, consistent with the presumed impact of limitations in neuropsychological functioning on everyday life. The results suggest that many subjects exposed to lead suffered acute encephalopathy in childhood which resolved into a chronic subclinical encephalopathy with associated cognitive dysfunction still evident in adulthood. These findings lend support to efforts to limit exposure to lead in childhood.